Characterising landscape homogenisation: a qualitative approach based on five case studies - Gonzalo Cortés-Capano; Girma Shumi; Kaisa J. Raatikainen; Zahra Mahdavi-Nezhad; Jacqueline Loos (Ecosystems and People)
Landscapes are places where multiple social-ecological relations thrive. However, due to intensification of industrial land-uses, they are losing their diversity of species and functions, languages and practices, thereby influencing the ways in which people interact with each other and non-human beings across the globe. A better understanding of such changes in landscapes is necessary to enhance urgent transformative change to overcome the sustainability crisis that humans and non-humans are currently facing. In this article, using an in-depth, reflexive thematic qualitative approach, we characterised landscape homogenisation across five case study landscapes in Ethiopia, Finland, Germany, Iran and Uruguay by a) identifying and describing the main driving forces underpinning landscape homogenisation within each landscape and b) exploring and discussing some of the main relations between different driving forces contributing to landscape homogenisation across landscapes. Four main driving forces characterising and contributing to landscape homogenisation globally emerged from the results: economic growth imperative; industrialised commodity production; rural depopulation; and abandonment of traditional practices. While all forces were observed across all studied landscapes, they took different shapes and ways in each context. We provide an operational conceptualisation of landscape homogenisation, highlight that the loss of landscape heterogeneity is driven by a complex fabric of co-occurring driving forces, and discuss potential constraints for transformative change. Our approach and lessons learned can provide insights to inform action-oriented research in other rural landscapes globally to addressing the interwoven nature of the issues challenging landscapes’ sustainability.